AMDAL SEBAGAI INSTRUMEN DALAM MEMPERTAHANKAN SUSTAINABLE DEVELOPMENT YANG BERWAWASAN LINGKUNGAN - Sari, Indah (JURNAL ILMIAH HUKUM DIRGANTARA, 2018)
This writing intends to explain what is AMDAL, what is its function and also its aim. It is also explain here about the role of AMDAL as an instrument to implement sustainable development policy with its environmental orientation. The crucial role of AMDAL is to keep developmental improvement proceed to sustainable development principles. State need to make a good developmental plan in which it is easier for societies and also governmental institutions to predict its significant impact after the plan being implemented. Developmental processes eventually need to based on AMDAL in considering sustainability of our generation and also next generation life. It is all stated in Act No 32 Year 2009 of Protection and Management of Environment and also in Governmental Regulation No 27 Year 1999 of Environmental Impact Analysis. Keywords: AMDAL, Sustainable Development, Environment, Act No 32 Year 2009